Hemophagocytic Lymphohistiocytosis and Gastrointestinal Bleeding: What a Surgeon Should Know - S. Popeskou; M. Gavillet; N. Demartines; D. Christoforidis (Case Reports in Surgery)
This paper presents to the surgical community an unusual and often ignored cause of gastrointestinal bleeding. Hemophagocytic syndrome or hemophagocytic lymphohistiocytosis (HLH) is a rare medical entity characterized by phagocytosis of red blood cells, leucocytes, platelets, and their precursors in the bone marrow by activated macrophages. When intestinal bleeding is present, the management is very challenging with extremely high mortality rates. Early diagnosis and treatment seem to be the most important factors for a successful outcome. We present two cases and review another 18 from the literature.